Income inequality, redistribution and domestic terrorism. (April 2019) - Krieger, Tim; Meierrieks, Daniel
Highlights: Analysis of the effect of income inequality on terrorism for a sample of 113 countries for the 1984–2012 period. More income inequality results in more domestic terrorism; IV-approaches yield similar results. Effect transmitted via negative effect of inequality on institutional quality (e.g., weaker rule of law). Redistribution is shown to be a powerful policy tool to reduce terrorism. Abstract: We analyze the effect of income inequality on terrorism for a sample of 113 countries between 1984 and 2012. We provide evidence, robust to various methodological changes (e.g., the use of instrumental-variable approaches), that higher levels of income inequality are associated with more domestic terrorism. Analyzing the underlying transmission channels, we find that this effect is in parts due to the ill effects of income inequality on institutional outcomes (e.g., corruption) which in turn motivate domestic terrorism. We also investigate whether redistributional efforts can be effective in reducing terrorist activity. We find that countries that redistribute more see less domestic terrorism, in parts because redistribution improves institutional conditions. In light of this latter finding, we discuss the implications of our analysis for policymakers who want to counter domestic terrorism through redistributive policies.